Short-term calorie and protein restriction provide partial protection from chemotoxicity but do not delay glioma progression - Brandhorst, Sebastian (2013)
Short-term starvation (STS) protects normal cells while simultaneously sensitizing malignant cells to high-dose chemotherapeutic drugs in mice and possibly patients. The fasting-dependent protection of normal cells and sensitization of malignant cells depends, in part, on reduced levels of insulin-like growth factor-1 (IGF-1) and glucose. Calorie restricted diets with defined macronutrient (carbohydrate, protein, fat) ratios were evaluated for the effects on stress sensitization markers and protection in mice treated with high-dose chemotherapy. We show that short-term CR significantly reduced both glucose and IGF-1 levels, but when specific macronutrient deficiencies were tested, only the complete lack of proteins reduced IGF-1 levels. Short-term 50% CR combined with either severe protein-deficiency or ketogenic diets improved chemotoxicity resistance similarly to the standard 50% CR, but did not result in the high protection caused by STS. Notably, a high protein diet reversed the beneficial effects of short-term CR. In a subcutaneous mouse model of glioma, feeding a low protein (4% calories from protein) diet for more than 20 days did not delay tumor progression once the tumor became palpable. Also, cycles of short-term (3 days) 50% CR did not augment the chemotherapy efficacy of cisplatin in a murine breast cancer model. These results indicate that the protection from chemotoxicity and retardation of the progression of certain tumors achieved with fasting is not obtained with short-term calorie and/or macronutrient restriction.